2016
DOI: 10.1177/1744806916674479
|View full text |Cite
|
Sign up to set email alerts
|

Spinal astrocytic activation contributes to mechanical allodynia in a rat model of cyclophosphamide-induced cystitis

Abstract: BackgroundPrevious studies have demonstrated that glial cells play an important role in the generation and maintenance of neuropathic pain. Activated glial cells produce numerous mediators such as proinflammatory cytokines that facilitate neuronal activity and synaptic plasticity. Similarly, bladder pain syndrome/interstitial cystitis shares many characteristics of neuropathic pain. However, related report on the involvement of spinal glia in bladder pain syndrome/interstitial cystitis-associated pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 61 publications
(96 reference statements)
1
30
0
1
Order By: Relevance
“…In our previous studies, we observed that the activation of astrocytes and microglia contribute to mechanical allodynia in CYP-induced cystitis model [8,9]. As far as we know, Iba1 and GFAP are the main markers of microglia and astrocytes, respectively.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In our previous studies, we observed that the activation of astrocytes and microglia contribute to mechanical allodynia in CYP-induced cystitis model [8,9]. As far as we know, Iba1 and GFAP are the main markers of microglia and astrocytes, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…Our previous study demonstrated that neuroinflammation in the spinal dorsal horn (SDH) might be associated to mechanism of interstitial cystitis, and contribute to mechanical allodynia [8,9]. Neuroinflammation is a complex and well-coordinated process consisting of various glial cells in the central nervous system (CNS) and peripheral immune cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cyclophosphamide (CYP)‐induced chronic pain, which is thought to be a visceral neuropathic pain syndrome, may be initiated and maintained in part by neuroinflammation‐leading central sensitization . Our previous study showed that glia cell activation can contribute to allodynia in CYP‐induced cystitis by releasing proinflammatory cytokines and inducing central sensitization at the spinal cord level …”
Section: Introductionmentioning
confidence: 99%
“…3 Our previous study showed that glia cell activation can contribute to allodynia in CYP-induced cystitis by releasing proinflammatory cytokines and inducing central sensitization at the spinal cord level. 4 Various important signaling pathways modulate neuroinflammation, leading to chronic pain. Neuregulin-1 (Nrg1)-ErbB signaling may be involved in this process.…”
Section: Introductionmentioning
confidence: 99%
“…Diversas outras teorias também propostas incluem a ativação mastocitária (31)(32)(33) , liberação de mediadores inflamatórios (34)(35)(36) , infecção subclínica (37) , alterações neuropáticas (38,39) , autoimunidade (40) , alteração da vascularização da bexiga (41) , causas psiquiátricas (42)(43)(44) e susceptibilidade genética (45,46) . Considerando a dificuldade de diagnóstico, a ampla variedade de apresentações e a associação da CI com outras doenças, é provável que ela represente uma síndrome com múltiplos mecanismos fisiopatológicos e fatores etiológicos.…”
Section: Critérios De Exclusão Niddk Para Definição De Cistite Intersunclassified